Calculati x•x+x+x:x=
(X+4)(x-3)-x+12=
3(x²-2x-2)+x(6-3x)=
(x•x²•x³•x⁴):x la a 10•x=
(2x+1)²-(2x-1)²=
(x²+x+1)²=
Va rog URGEEEENT
Răspunsuri la întrebare
Răspuns de
4
x^2+x+1
x^2-3x+4x-12-x+12=x^2
3x^2-6x-6+6x-3x^2=-6
x^10:x^10×x=1×x=x
(2x+1-2x+1)(2x+1+2x-1)=2×4x=8x
x^4+c^2+1+2x^3+2x^2+2x
x^2-3x+4x-12-x+12=x^2
3x^2-6x-6+6x-3x^2=-6
x^10:x^10×x=1×x=x
(2x+1-2x+1)(2x+1+2x-1)=2×4x=8x
x^4+c^2+1+2x^3+2x^2+2x
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă